A REVIEW OF SPONTANEOUS COMBUSTION OF COALS - (:unkn) unknown (MARCEL DEKKER INC, 1995)
Coal is one of the carbonaceous materials which, under certain conditions, can combust spontaneously as a result of its oxidation with atmospheric oxygen. Coal oxidation is an irreversible exothermic reaction and its rate increases with temperature. In mines or in storage, the deficiency of the heat dissipation capacity of the coal bulk with respect to its heat generation capacity can result in heat accumulation which subsequently leads to higher oxidation rates due to higher temperatures. This process, if not averted with appropriate action, results in the spontaneous combustion of the coal. The heat generation and dissipation capacities of a coal bulk depend on a number of factors. It is the outcome of the interactions between these factors that determines the occurrence or nonoccurrence of spontaneous combustion. This manuscript aims at presenting the fundamentals of spontaneous combustion together with a review of the findings and proposals on its causes, mechanism, associated factors and methods of prevention.
Keywords: LOW-TEMPERATURE OXIDATION; VICTORIAN BROWN COAL; BITUMINOUS COAL; MODEL; OXYGEN; WATER